1996
DOI: 10.1021/jo960982j
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Oligomerization of 3-(Alkylsulfanyl)thiophenes with Ferric Chloride

Abstract: The action of FeCl(3) on 3-(alkylsulfanyl)thiophenes (3-(alkylthio)thiophenes) leads to the one-step formation of regioregular alpha-conjugated oligothiophenes, from trimer to octamer, depending on the solvent used and on the length of the alkyl chain. The regiochemistry of these oligomers is characterized by one inner head-to-head linkage between adjacent rings and by a variable number of lateral head-to-tail junctions. The reaction of ferric chloride with the head-to-head and head-to-tail bis(methylsulfanyl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…[35] Mustafa and Shephered reported a simple dimerization of β-trimethylsilyl-substituted terthiophenes using ceric ammonium nitrate (CAN). [36] Recently, Kita and co-workers reported a synthesis of 2,2Ј-bithiophene derivatives that involved oxidative coupling of the corresponding alkylthiophenes using a combination of phenyl iodide bis(trifluoroacetate) and BF 3 ·OEt 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[35] Mustafa and Shephered reported a simple dimerization of β-trimethylsilyl-substituted terthiophenes using ceric ammonium nitrate (CAN). [36] Recently, Kita and co-workers reported a synthesis of 2,2Ј-bithiophene derivatives that involved oxidative coupling of the corresponding alkylthiophenes using a combination of phenyl iodide bis(trifluoroacetate) and BF 3 ·OEt 2 .…”
Section: Resultsmentioning
confidence: 99%
“…However, Barbarella et al reported interesting results producing regioregular oligothiophenes from 3-alkylsulfanylthiophene through oxidative coupling using FeCl 3 . 11 In their report, oligothiophenes from trimer to octamer were formed depending on the reaction conditions. All the oligothiophenes possessed a regioregular structure with one HH linkage and all remaining HT linkages.…”
Section: Discussionmentioning
confidence: 99%
“…Two pathways can be considered for the synthesis of long polymer chains: monomer ± oligomer and oligomer ± oligomer reactions. It is generally accepted that the former is predominant, and several experimental observations, such as the structural differences between polypyrrole and poly(bipyrrole) and the recent work of Barbarella et al [9] on the oligomerization of 3-(alkylsulfanyl)thiophenes, support this idea. However, it was also demonstrated that terpyrrole, bipyrrole, and pyrrole radical cations have similar lifetimes in acetonitrile [10] (rate constants for dimerization: 5 Â 10 8 , 1.2 Â 10 9 , and ca.…”
Section: Introductionmentioning
confidence: 99%